2020
DOI: 10.2323/jgam.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic actinomycetes associated with <i>Cinnamomum cassia</i> Presl in Hoa Binh province, Vietnam: Distribution, antimicrobial activity and, genetic features

Abstract: Endophytic microbes associated with medicinal plants are considered to be potential producers of various bioactive secondary metabolites. The present study investigated the distribution, antimicrobial activity and genetic features of endophytic actinomycetes isolated from the medicinal plant Cinnamomum cassia Presl collected in Hoa Binh province of northern Vietnam. Based on phenotypic characteristics, 111 actinomycetes were isolated from roots, stems and leaves of the host plants by using nine selective media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
(79 reference statements)
1
18
0
Order By: Relevance
“…This is the potential source for the isolation of endophytic actinomycetes producing valuable secondary metabolites. Unfortunately, so far very few studies on the distribution and biological characteristics of endophytic actinomycetes from medicinal plants in Vietnam have been published (Phan et al, 2016;Lam, 2017;Vu et al, 2019). In this context, the present study focused on the endophytic actinomycete population associated with Cinnamomum cassia Presl which is widely used in Vietnam as traditional medicine regimen for treating various infections and chronic diseases as well.…”
Section: Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the potential source for the isolation of endophytic actinomycetes producing valuable secondary metabolites. Unfortunately, so far very few studies on the distribution and biological characteristics of endophytic actinomycetes from medicinal plants in Vietnam have been published (Phan et al, 2016;Lam, 2017;Vu et al, 2019). In this context, the present study focused on the endophytic actinomycete population associated with Cinnamomum cassia Presl which is widely used in Vietnam as traditional medicine regimen for treating various infections and chronic diseases as well.…”
Section: Screeningmentioning
confidence: 99%
“…The YIM38 culture broth of actinomycete strains were centrifuged at 10.000 rpm/min for 10 min, then the supernatances were passed 0.22 µL filters. The cell-free supernatants of Streptomyces strains were used for the evaluation of antimicrobial activity against the nine microbes using the agar well diffusion method as described before (Vu et al, 2018;Vu et al, 2019). The experiments were performed in triplicates.…”
Section: Screening For Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activity of S. cavourensis YBQ59 against the nine microbes (mentioned above) was performed by using the agar well diffusion method as described previously [3,7,8]. The experiments were performed in triplicates.…”
Section: Antimicrobial Activity Testing and Cytotoxic Assaymentioning
confidence: 99%
“…Furthermore, rich-EO-content medicinal plants like L. cubeba and Cinnamomum spp. could also be one of the prevalent sources for antibiotic-producing endophytic actinobacteria conveying novel features [12,13]. In fact, it has been previously demonstrated that the ecology and evolution of endophytic microorganisms might be affected by the chemical compositions of host plant EO and the participation of endophytes in the biotransformation of EO [14].…”
Section: Introductionmentioning
confidence: 99%